2011
DOI: 10.4018/jmhci.2011100104
|View full text |Cite
|
Sign up to set email alerts
|

Experimenting Through Mobile ‘Apps’ and ‘App Stores’

Abstract: Utilizing App Stores as part of an ‘in-the-large’ methodology requires researchers to have a good understanding of the effects the platform has in the overall experimental process if they are to utilize it effectively. This paper presents an empirical study of effects of the operation an App Store has on an App lifecycle through the design, implementation and distribution of three games on the WidSets platform which arguably pioneered many of the features now seen as conventional for an App Store. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Last but not least, Coulton and Bamford (2011), report on experiences with applications released to the WidSet platform, with two deployed applications with a total of more than 1.4 million users. Data collection was begun in October 2007, and -to the best of our knowl-edge -this constitutes the first and largest conducted study to be reported.…”
Section: Informing the Research Approachmentioning
confidence: 99%
“…Last but not least, Coulton and Bamford (2011), report on experiences with applications released to the WidSet platform, with two deployed applications with a total of more than 1.4 million users. Data collection was begun in October 2007, and -to the best of our knowl-edge -this constitutes the first and largest conducted study to be reported.…”
Section: Informing the Research Approachmentioning
confidence: 99%
“…As the current application was developed using FlashLite it is easily portable to AIR, making this a logical decision for progression. For Big Game Huntr to succeed on a global scale it is apparent that the game should be optimised to appear on a wide range of platforms, especially those leading the way in current market trends (Android and iOS), and that have a greater presence in western markets (Coulton & Bamford, 2010). This will give a broader representation of the global response to the game as a wider range of countries will then be catered for.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Over the last decade, the exponential rise of mobile device ownership, the creation of the 'app store' and lower barriers to entry has propelled mobile gaming to be the leading entertainment factor amongst mobile device usage [5]. However, due to the nature of said personal devices they tend to isolate its users, whereas console and board games promotes social interactions via online play functionalities (i.e.…”
Section: Paper and Mobile Revolutionmentioning
confidence: 99%